Pengaruh Model Pictorial Riddle Berbantuan Aplikasi Canva Terhadap Kemampuan Literasi Sains Siswa SD Materi Sifat-Sifat Benda - Ariefka, Reza; Ariyanti, Etika (LPPPI Publishing, 2025)
This study aims to analyze the effect of the Pictorial Riddle learning model assisted by the Canva application on the scientific literacy skills of elementary school students on the material properties of objects. This study uses a quantitative method with a True Experimental Design. The research sample consisted of 22 fifth-grade students of SD Negeri 1 Karang Melati, which were divided into an experimental class (11 students) and a control class (11 students). The pre-test results showed an average score of 55.63 in the experimental class and 51.81 in the control class. After treatment, the post-test results increased to 73.18 in the experimental class and 61.81 in the control class. The Paired Sample T-Test test showed a significant difference between the pre-test and post-test with a sig. Value of 0.001 (<0.05), while the Independent Sample T-Test test showed a significant difference between the experimental and control classes with a sig. Value of 0.000 (<0.05). The results of this study indicate that the Pictorial Riddle model assisted by Canva significantly improves students' scientific literacy skills.